Correlation of surface roughness, tool wear, and chip slenderness ratio in the lathe process of aluminum alloy – 6061 - Sudjatmiko, Sudjatmiko; Soenoko, Rudy; Suprapto, Agus; Choiron, Moch Agus (Eastern-European Journal of Enterprise Technologies, 2019)
The research on the lathe process has described that the tool nose radius parameter is one of the factors that has an influence on surface roughness in the form of product quality. Chip slenderness ratio is an important parameter in the lathe process that can be applied theoretically or empirically. The lathe process was carried out on the Aluminum Alloy – 6061 material, the effects of the selected responses, namely surface roughness (SR), surface area of tool wear (Vb), and chip slenderness ratio (δ) were investigated. The selection of the main cutting tool nose radius (ns), spindle speed (n), feeding speed (vf), and depth of cut (a) can affect surface roughness which were conditioned to be constant, can influence chip shape and chip slenderness ratio and surface area of tool flank wear. The chip shape in the lathe process has a correlation with the product surface roughness, the chip slenderness ratio, and the tool flank wear. In this study, the experimental investigation and statistical analysis used the Taguchi experimental design method of L9 (34) orthogonal array, and the parameters used in the lathe cutting process of Aluminum Alloy – 6061 were tool angle, spindle speed, depth of cut and feed rate that affected the response results ((SR), (δ), and Vb). The contribution of each factor to the output is determined by variance analysis. Using ANOVA, the multiregression model is obtained by the relationship between the factors (ns, n, vf, and a) on the response (SR, δ, and Vb), expressed by the following equation: SR=0.955556+0.074444ns+0.006667n+0.005556vf–0.001111a, δ=7.18889–1.17556ns–0.59222n–0.60222vf–0.09111a, and Vb=0.320370–0.073704ns–0.021481n–0.041481vf–0.032593a. Correlation results found that: (a) tool nose radius of 0.4 mm, feeding speed 56 mm/min, and cutting depth of 0.25 mm had an influence on SR=1.11 µm, (b) tool nose radius of 1.2 mm, feeding speed 58 mm/min and the depth of cut of 0.25 mm have an influence on δ=7.07, (c) tool nose radius of 0.4 mm, feeding speed of 60 mm/min, and cutting depth of 0.50 mm have an influence on Vb=0.34 mm2. The conclusion is that the effect on the correlation of the R2 value is very strong against SR=97.89 %, δ=94.45 % and Vb=67.30 %